UJI ANTIBAKTERI EKSTRAK BUAH TAKOKAK (SOLANUM TORVUM SWARTZ) TERHADAP PERTUMBUHAN BAKTERI PROPIONIBACTERIUM ACNES - Merta Meliana Lajira; I Nyoman Ehrich Lister (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2019)
Acne vulgaris is a disorder of the skin characterized by changes in blackheads, papules, pustules, and nodules that often occur on the face, shoulders, and back. Propionibacterium acnes is the main habitat that contributes to acne. One of the plants that have an anti-bacterial effect is takokak fruit. This study aims to study the presence or absence of anti-bacterial effects of takokak fruit extract on the growth of Propionibacterium acne bacteria. The test method used is the Diplo disk diffusion method. The fruit was extracted by maceration method using ethanol as a solvent and then diluted using 96% ethanol at a concentration of 25%, 50%, 75%, 100% while the positive control used a clindamycin suspension and negative control of distilled water. The results showed that takokak fruit extract had an antibacterial effect on Propionibacterium acnes with an average diameter inhibition zone of 16.75 mm; 18.3 mm; 18.85 mm; 21.92 mm. Positive control (clindamycin) 37,45; negative control (distilled water) has no value to prevent bacteria.